Clinical Flexibility : A Graduate-Clinician Focus Group - McDonald, Melissa (My University, 2014)
The purpose of this study was to examine clinical flexibility, a skill that is essential in a field that requires clinicians to provide individualized services, rather than applying cookbook approaches. A focus group, comprised of second-year graduate students, explored student learning preferences as they relate to prior knowledge, flexibility, and theoretical perspectives.
Color poster with text and images.
Keywords: Speech-language pathologists; Focus groups; Clinical flexibility; Posters